An Overview on Parkinsons Hyperpyrexia Syndrome: Efficacy of Single Dose - Sannegowda, Raghavendra Bakki; Mohammed, Najeeb Behzad; Hejamadi, Mohammed Ismail; Sharma, Bhawna; Dubey, Parul (Medicine and Medical Research: New Perspectives Vol. 9, 2024)
Parkinsonism-hyperpyrexia syndrome (PHS) is a neurological emergency that mimics neuroleptic malignant syndrome and sepsis. Abrupt cessation of anti parkinsons drugs, usually levodopa is responsible for this syndrome. This study reports a case of a 70-year-old male with a history of diabetes mellitus (managed with insulin), hypertension, and Parkinson's disease, who presented with sudden onset of fever, altered sensorium, and exacerbated parkinsonian features over the past day. Relative dopamine deficiency is a proposed mechanism for PHS and the replacement of dopaminergic drugs is the mainstay of treatment. Missing even a single dose of levodopa can precipitate PHS, highlighting the importance of early identification, which can be life-saving. While sudden cessation of levodopa is linked to a relative dopamine deficiency state that leads to PHS—a mimic of neuroleptic malignant syndrome—there remains uncertainty about how abrupt the cessation must be or how many doses need to be missed to trigger these symptoms. Our case is an eye-opener to show that missing even a single dose of levodopa can induce PHS, a potentially preventable and treatable condition that if untreated can mimic sepsis and is fatal.